Comparison of the Incidence of Preterm Labor Between Pregnant Woman with Systemic Lupus Erythematosus Mild and Moderate-Savere - Pradani, Yulistiya Kusuma; Bachnas, Muhammad Adianes; Aryoseto, Lukman; Laqif, Abdurahman (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2024)
Background: Systemic Lupus Erythematosus (SLE) is an autoimmune disease that can affect pregnancy, particularly by increasing the risk of preterm birth. This condition can be influenced by various factors, including the level of SLE activity. Therefore, this study aims to analyze the relationship between preterm birth and the activity level of SLE categorized as mild and moderate-to-severe. Subjects and Method: This study used an analytical observational technique with a cross-sectional research design based on medical record data of pregnant women with SLE at Dr. Moewardi Hospital in the 2021-2023 period, selected through consecutive sampling This study involved 77 pregnant patients with SLE. The dependent variable is preterm labor. The independent variable in this study is pregnant women with SLE. The data were collected by medical record. The data were analyzed by Fisher’s exact test. Results: There was no significant association between the degree of systemic lupus erythematosus activity and preterm labor (p= 0.759). Conclusion: This study shows that there is no significant relationship between the incidence of preterm labor and the degree of systemic lupus erythematosus activity (mild and moderate-to-severe).